2020
DOI: 10.1021/acs.joc.9b03251
|View full text |Cite
|
Sign up to set email alerts
|

O-Perfluoropyridin-4-yl Oximes: Iminyl Radical Precursors for Photo- or Thermal-Induced N–O Cleavage in C(sp2)–C(sp3) Bond Formation

Abstract: O-Perfluoropyridin-4-yl group was first installed onto cycloketone oximes as a new electrophore, which was proven to be efficient iminyl radical precursors under photocatalytic and thermal conditions. A range of O-perfluoropyridin-4-yl oximes were successfully utilized in C­(sp2)–C­(sp3) bond formations of quinoxalin-2­(1H)-ones and alkenes, providing facile accesses to a range of functionalized alkylnitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…At the same time, Xu and co‐workers reported that the cyanoalkylation of quinoxalinones could also be conducted in DMF with fac ‐Ir(ppy) 3 as the photocatalyst [66] . Recently, Yang and co‐workers have realized cyanoalkylation of quinoxalinones by using O ‐perfluoropyridinn‐4‐yl oximes as the cyanoalkyl source [67] . Guided by the same principle, Xia and co‐workers discovered that the cyanoalkylation protocol could be extended to other nitrogen‐bearing heterocycle including isoquinolines and quinolines [68] …”
Section: Photocatalyzed Cross‐couplings Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, Xu and co‐workers reported that the cyanoalkylation of quinoxalinones could also be conducted in DMF with fac ‐Ir(ppy) 3 as the photocatalyst [66] . Recently, Yang and co‐workers have realized cyanoalkylation of quinoxalinones by using O ‐perfluoropyridinn‐4‐yl oximes as the cyanoalkyl source [67] . Guided by the same principle, Xia and co‐workers discovered that the cyanoalkylation protocol could be extended to other nitrogen‐bearing heterocycle including isoquinolines and quinolines [68] …”
Section: Photocatalyzed Cross‐couplings Reactionsmentioning
confidence: 99%
“…[66] Recently, Yang and co-workers have realized cyanoalkylation of quinoxalinones by using O-perfluoropyridinn-4-yl oximes as the cyanoalkyl source. [67] Guided by the same principle, Xia and coworkers discovered that the cyanoalkylation protocol could be extended to other nitrogen-bearing heterocycle including isoquinolines and quinolines. [68] A radical cascade cyclization of aryl isonitriles 156 and cycloketone oxime esters 155 with fac-Ir(ppy) 3 as the photocatalyst in DMAc was demonstrated by Zhang and co-workers (Scheme 53).…”
mentioning
confidence: 99%
“…To conclude the reports on photoredox-triggered cyanopropylation of quinoxalin-2-ones using redox-active cyclobutanone oxime esters, at early 2020, Yang's research team reported a synthetic protocol. [36] In the abovementioned work, a set of γcyanopropylated quinoxalin-2-ones were synthetized using a perfluoropyridin-based redox active cyclobutanone oxime. Although they only described sixteen quinoxalin-2-one-derived examples (Scheme 14), they conducted a lot of experiences in order to gain insight in the reaction mechanism, as well as a comparison of the generation of the desired radical under thermal reaction conditions.…”
Section: Eurjocmentioning
confidence: 99%
“…In just six months, four similar methodologies were reported and, surprisingly, the first one in the chronological line was the most sustainable, because of the use of Eosin Y as photoredox catalyst, avoiding the use of expensive and toxic metals complexes. Regarding the scope of the reaction, the two Xin Li's works showed a broad scope, particularly in the design and use of complex redox-active oximes, while the labour of Yang [36] and collaborators goes deeper into the mechanistic aspects of this transformation.…”
Section: Eurjocmentioning
confidence: 99%
See 1 more Smart Citation